Electroweak phase transition in a complex singlet extension of the Standard Model with degenerate scalars - Gi-Chol Cho (Elsevier, 2021)
We study the feasibility of strong first-order electroweak phase transition (EWPT) in a degenerate-scalar scenario of a complex singlet extension of the Standard Model, in which a mass of an additional scalar is nearly degenerate with that of the Higgs boson, 125 GeV. This scenario is known to provide an exquisite solution for circumventing constraints from dark matter direct detection experiments due to cancellations between two scattering amplitudes mediated by two scalars. In the analysis of EWPT, we employ two gauge-invariant calculation schemes on the scalar potential and two familiar resummation methods in evaluating one-loop (gauge dependent) effective potential. We point out that one of the conditions for the strong first-order EWPT is incompatible with the known suppression mechanism of a dark matter cross-section scattering off the nucleons. Nevertheless, we find that strong first-order EWPT is still possible in the degenerate-scalar scenario by dodging dark matter constraints differently.